2021
DOI: 10.1007/s12325-021-01761-3
|View full text |Cite|
|
Sign up to set email alerts
|

Vaccine Considerations for Multiple Sclerosis in the COVID-19 Era

Abstract: People with multiple sclerosis (MS) are at risk for infections that can result in amplification of baseline symptoms and possibly trigger clinical relapses. Vaccination can prevent infection through the activation of humoral and cellular immune responses. This is particularly pertinent in the era of emerging novel vaccines against severe acute respiratory syndrome coronavirus 2, the virus that causes coronavirus disease 2019 (COVID-19). MS disease-modifying therapies (DMTs), which affect the immune system, may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 140 publications
1
37
0
Order By: Relevance
“…Patients with multiple sclerosis (MS) have an increased risk of respiratory infections, especially patients presenting severe disability and on disease-modifying treatments (DMTs) (1). Infections can trigger MS relapses (2), and thus, vaccination in MS patients should be pursued as a general policy in order to reduce the risk of infections (3). Despite the long-standing debate over an increased risk of relapse occurrence after vaccination, the existence of this phenomenon has not been confirmed (4).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with multiple sclerosis (MS) have an increased risk of respiratory infections, especially patients presenting severe disability and on disease-modifying treatments (DMTs) (1). Infections can trigger MS relapses (2), and thus, vaccination in MS patients should be pursued as a general policy in order to reduce the risk of infections (3). Despite the long-standing debate over an increased risk of relapse occurrence after vaccination, the existence of this phenomenon has not been confirmed (4).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with MS, especially those with the severe forms of the disease, have a higher risk for acquiring certain types of viral and bacterial infections. It has been shown that there is a link between bacterial and viral infections and greater chance of occurrence of relapses or pseudo-relapses in MS patients [34][35][36][37]. Additionally, almost all MS patients are under treatment with immunomodulatory or immuno-suppressive disease-modifying therapies (DMTs) to lessen disease activity, severity and to prevent or slow disease progression.…”
Section: Multiple Sclerosis and Infectionsmentioning
confidence: 99%
“…COVID-19-related MS mortality has been reported to be approximately 1–4%. 323 Several studies have shown that some DMTs are associated with increased risk of COVID-19. However, patients who are not receiving DMTs have also been shown as a high risk for COVID-19 infection in some studies.…”
Section: Covid-19 Vaccination In Immunocompromised Patientsmentioning
confidence: 99%